Analysis of The Effectiveness of The Distribution of Mosque Zakat Funds - Almustofa, Sodiq; Amarudin, Amin Awal; Muna, Naily El (Universitas Trunojoyo Madura, 2024)
The mosque as the center of Islamic civilization is not only the center of worship ceremonies but also can be the center of the economy, by making the mosque one of the zakat management bodies/institutions. As has been done by the management of the Jogokariyan Mosque, Yogyakarta Special Region. In this study, the problem is how high the level of effectiveness of zakat distribution is in Baitul Maal Masjid Jogokariyan. The purpose of this research is to measure the effectiveness level of zakat fund distribution in Baitul Maal Masjid Jogokariyan. This research uses a descriptive qualitative method by using the Zakat Core Principles (ZCP) model. The object used in this research is the financial statements of Baitul Maal Masjid Jogokariyan for one year from April 1, 2022, to March 31, 2023. Based on the calculation of the effectiveness level of Baitul Maal Masjid Jogokariyan of 78% (seventy-eight percent), this shows that the effectiveness level of Baitul Maal Masjid Jogokariyan is effective where in the DCR (Disbursement Collection Ratio) category reaches 78%.